Causal relationship between type 2 diabetes mellitus and cognitive impairment based on Mendelian randomization - LIN Yijia; CHENG Lizhen; HU Tingjun; MIAO Ya (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To investigate the causal relationship between type 2 diabetes mellitus (T2DM) and cognitive dysfunction using two-sample Mendelian randomisation (MR).Methods·Instrumental variables associated with T2DM were pooled from a large-scale genome-wide association study (GWAS) dataset. Inverse variance weighting was used as the primary analytical technique, supplemented by MR-Egger regression, weighted median and simple median analyses. Meta-analysis was jointly applied to combine different endpoints and to analyse the possibility of a causal relationship between T2DM and dementia, Alzheimer's disease, and Parkinson's dementia. Horizontal pleiotropy was examined by MR-PRESSO global test and MR-Egger analysis.Results·There was a causal relationship between genetically predicted T2DM and dementia (OR=1.11, 95%CI 1.02~1.20, P=1.96×10-2) and AD (OR=1.16, 95%CI 1.04~1.30, P=8.41×10-3). Meta-analysis also supported the association between T2DM and cognitive impairment (OR=1.12, 95%CI 1.05~1.20, P=4.22×10-4). A series of sensitivity analyses suggested the absence of heterogeneity and horizontal pleiotropy. Reverse MR analysis showed no significant causal relationship of various types of dementia on T2DM.Conclusion·T2DM is positively associated with the risk of developing various types of dementia, suggesting that T2DM may be an important risk factor for cognitive impairment.